Mekepung Jembrana Tradition As a Source of Creation of Documentary Film - Yogantara, Wayan Arfian; Mudra, I Wayan; Swandi, I Wayan (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2024)
The Mekepung tradition in Jembrana, Bali, particularly in the form of buffalo racing, is a deeply rooted cultural spectacle representing joy and celebration for agrarian communities. This research aims to explore this tradition and create a documentary film to preserve and promote its significance. Employing a qualitative descriptive method and utilizing the documentary film structure approach, the study incorporates observation, interviews, and documentation to gather authentic data. The documentary follows a three-part story structure, capturing the essence of Mekepung through genuine visual presentations and a well-structured narrative flow. Embracing a performative documentary style, the film emphasizes captivating packaging and meticulous craftsmanship. The creation process encompasses pre-production, production, and post-production stages. Ultimately, the Mekepung Jembrana documentary not only showcases buffalo racing but also serves as a vital tool for cultural preservation and awareness for future generations, ensuring the continuity of this cherished tradition.